In Vitro Inhibition of the Mycobacterium tuberculosis β-Ketoacyl-Acyl Carrier Protein Reductase MabA by Isoniazid - Ducasse-Cabanot, Stéphanie (American Society for Microbiology, 2004)
The first-line specific antituberculous drug isoniazid inhibits the fatty acid elongation system (FAS) FAS-II involved in the biosynthesis of mycolic acids, which are major lipids of the mycobacterial envelope. The MabA protein that catalyzes the second step of the FAS-II elongation cycle is structurally and functionally related to the in vivo target of isoniazid, InhA, an NADH-dependent enoyl-acyl carrier protein reductase. The present work shows that the NADPH-dependent β-ketoacyl reduction activity of MabA is efficiently inhibited by isoniazid in vitro by a mechanism similar to that by which isoniazid inhibits InhA activity. It involves the formation of a covalent adduct between Mn(III)-activated isoniazid and the MabA cofactor. Liquid chromatography-mass spectrometry analyses revealed that the isonicotinoyl-NADP adduct has multiple chemical forms in dynamic equilibrium. Both kinetic experiments with isolated forms and purification of the enzyme-ligand complex strongly suggested that the molecules active against MabA activity are the oxidized derivative and a major cyclic form. Spectrofluorimetry showed that the adduct binds to the MabA active site. Modeling of the MabA-adduct complex predicted an interaction between the isonicotinoyl moiety of the inhibitor and Tyr185. This hypothesis was supported by the fact that a higher 50% inhibitory concentration of the adduct was measured for MabA Y185L than for the wild-type enzyme, while both proteins presented similar affinities for NADP(+). The crystal structure of MabA Y185L that was solved showed that the substitution of Tyr185 induced no significant conformational change. The description of the first inhibitor of the β-ketoacyl reduction step of fatty acid biosynthesis should help in the design of new antituberculous drugs efficient against multidrug-resistant tubercle bacilli.